2009
DOI: 10.1007/s12291-009-0022-1
|View full text |Cite
|
Sign up to set email alerts
|

Whether western normative laboratory values used for clinical diagnosis are applicable to Indian population? An overview on reference interval

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
(37 reference statements)
1
10
0
Order By: Relevance
“…Such changes are known to influence hormone levels. Further, international guidelines have recommended the establishment of reference intervals for every country and the lack of such studies in India has been recently reported (12). In the present study, the various reference hormone values measured using EIA/ELISA were within the physiological range for each ethnic group in subjects between 20 to 50 years of age.…”
Section: Discussionsupporting
confidence: 58%
“…Such changes are known to influence hormone levels. Further, international guidelines have recommended the establishment of reference intervals for every country and the lack of such studies in India has been recently reported (12). In the present study, the various reference hormone values measured using EIA/ELISA were within the physiological range for each ethnic group in subjects between 20 to 50 years of age.…”
Section: Discussionsupporting
confidence: 58%
“…International guidelines recommend that every country must establish reference intervals for healthy individuals belonging to a group of homogeneous population. Considering enormous racial and ethnic diversity of Indian population, it is mandatory to establish reference intervals specific to Indian population [1].…”
Section: Measurement Of Prolactinmentioning
confidence: 99%
“…The values are obtained by observation or measurement of a particular type of quantity on reference individuals who are selected, as basis for comparison with individuals under clinical investigation, through the use of defined criteria [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In India, clinical laboratories use the reference values of commonly used analytes supplied by diagnostic reagent and equipment manufacturers in their instructions without giving details of the original source of the data [10]. Currently used RI for liver enzymes levels in India are mainly based upon western population and those provided by manufacturer of kits.…”
Section: Introductionmentioning
confidence: 99%